A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India, with cladistic analysis and a world key to the known males - Mondal, Debarshi; Mukherjee, Tuhar; Hazra, Niladri (Zootaxa, 2020)
A new species of the genus Larsia Fittkau, 1962 is described based on the adult males. It is the first species of this genus reported from India and second member from the Oriental region. The DNA barcode of this new species is provided. The cladistic analysis of the known species of Larsia using morphological data of both immature and male adult stages have supported monophyly of the genus. A world key to the known males of the genus Larsia is presented here.